Eastern Afromontane Ecosystem Profile Summary: English to Arabic translate booklet (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
About CEPF:Â Established in 2000, the Critical Ecosystem Partnership Fund (CEPF) is a globalÂ leader in enabling civil society to participate in and influence the conservation ofÂ some of the worldâ€™s most critical ecosystems. CEPF is a joint initiative of lâ€™AgenceÂ FranÃ§aise de DÃ©veloppement (AFD), Conservation International, the GlobalEnvironment Facility (GEF), the Government of Japan, the John D. and CatherineÂ T. MacArthur Foundation and the World Bank. CEPF is unique among fundingÂ mechanisms in that it focuses on high-priority biological areas rather thanÂ political boundaries and examines conservation threats on a landscape scale.Â From this perspective, CEPF seeks to identify and support a regional, rather thana national, approach to achieving conservation outcomes and engages a wideÂ range of public and private institutions to address conservation needs throughcoordinated regional efforts.Ù†Ø¨Ø°Ø© Ø¹Ù† ØµÙ†Ø¯ÙˆÙ‚ Ø´Ø±Ø§ÙƒØ© Ø§Ù„Ø£Ù†Ø¸Ù…Ø© Ø§Ù„Ø¨ÙŠØ¦ÙŠØ© Ø§Ù„Ù‡Ø§Ù…Ø©ØªØ£Ø³Ø³ ØµÙ†Ø¯ÙˆÙ‚ Ø´Ø±Ø§ÙƒØ© Ø§Ù„Ø£Ù†Ø¸Ù…Ø© Ø§Ù„Ø¨ÙŠØ¦ÙŠØ© Ø§Ù„Ù‡Ø§Ù…Ø© Ø¹Ø§Ù… 2000 ØŒ ÙˆÙŠØ¹ØªØ¨Ø± Ù…Ù† Ø§Ù„Ø±ÙˆØ§Ø¯ Ø§Ù„Ø¯ÙˆÙ„ÙŠÙŠÙ† ÙÙŠ ØªÙ…ÙƒÙŠÙ† Ø§Ù„Ù…Ø¬ØªÙ…Ø¹Ø§Ù„Ù…Ø¯Ù†ÙŠ Ù…Ù† Ø§Ù„Ù…Ø´Ø§Ø±ÙƒØ© ÙˆØ§Ù„ØªØ£Ø«ÙŠØ± ÙÙŠ Ø§Ù„ØÙØ§Ø¸ Ø¹Ù„Ù‰ Ø¨Ø¹Ø¶ Ø§Ù„Ø£Ù†Ø¸Ù…Ø© Ø§Ù„Ø¨ÙŠØ¦ÙŠØ© Ø§Ù„Ø£ÙƒØ«Ø± Ø£Ù‡Ù…ÙŠØ© ÙÙŠ Ø§Ù„Ø¹Ø§Ù„Ù…. ÙŠÙ…Ø«Ù„Ø§Ù„ØµÙ†Ø¯ÙˆÙ‚ Ù…Ø¨Ø§Ø¯Ø±Ø© Ù…Ø´ØªØ±ÙƒØ© Ø¨ÙŠÙ† Ø§Ù„ÙˆÙƒØ§Ù„Ø© Ø§Ù„ÙØ±Ù†Ø³ÙŠØ© Ù„Ù„Ø¥Ù†Ù…Ø§Ø¡ Ùˆ Ù…Ù†Ø¸Ù…Ø© Ø§Ù„ØÙ…Ø§ÙŠØ© Ø§Ù„Ø¯ÙˆÙ„ÙŠØ© Ùˆ Ù…Ø±ÙÙ‚ Ø§Ù„Ø¨ÙŠØ¦Ø©Ø§Ù„Ø¹Ø§Ù„Ù…ÙŠ ÙˆØÙƒÙˆÙ…Ø© Ø§Ù„ÙŠØ§Ø¨Ø§Ù† Ùˆâ€Ù…Ø¤Ø³Ø³Ø© Ø¬ÙˆÙ† Ø¯. ÙˆÙƒØ§Ø«Ø±ÙŠÙ† Øª. Ù…ÙƒØ¢Ø±Ø«Ø±â€ ÙˆØ§Ù„Ø¨Ù†Ùƒ Ø§Ù„Ø¯ÙˆÙ„ÙŠ.ÙŠØªÙ…ÙŠØ² ØµÙ†Ø¯ÙˆÙ‚ Ø´Ø±Ø§ÙƒØ© Ø§Ù„Ø£Ù†Ø¸Ù…Ø© Ø§Ù„Ø¨ÙŠØ¦ÙŠØ© Ø§Ù„Ù‡Ø§Ù…Ø© Ø¹Ù† ØºÙŠØ±Ù‡ Ù…Ù† Ø¢Ù„ÙŠØ§Øª Ø§Ù„ØªÙ…ÙˆÙŠÙ„ Ø¨ØªØ±ÙƒÙŠØ²Ù‡ Ø¹Ù„Ù‰ Ù…Ù†Ø§Ø·Ù‚Ø§Ù„ØªÙ†ÙˆØ¹ Ø§Ù„ØÙŠÙˆÙŠ Ø°Ø§Øª Ø§Ù„Ø£ÙˆÙ„ÙˆÙŠØ© Ø§ÙƒØ«Ø± Ù…Ù† ØªØ±ÙƒÙŠØ²Ù‡ Ø¹Ù„Ù‰ Ø§Ù„ØØ¯ÙˆØ¯ Ø§Ù„Ø³ÙŠØ§Ø³ÙŠØ© Ø¨Ø§Ù„Ø¥Ø¶Ø§ÙØ© Ø§Ù„Ù‰ Ø§Ø®Ø°Ù‡ Ø¨Ø¹ÙŠÙ† Ø§Ù„Ø¥Ø¹ØªØ¨Ø§Ø±Ø§Ù„ØªÙ‡Ø¯ÙŠØ¯Ø§Øª Ø§Ù„Ø¨ÙŠØ¦ÙŠØ© Ø¹Ù„Ù‰ Ù†Ø·Ø§Ù‚ Ø¬ØºØ±Ø§ÙÙŠ ÙˆØ§Ø³Ø¹. ÙˆÙ…Ù† Ù‡Ø°Ø§ Ø§Ù„Ù…Ù†Ø¸ÙˆØ±ØŒ ÙŠØ³Ø¹Ù‰ Ø§Ù„ØµÙ†Ø¯ÙˆÙ‚ Ø¥Ù„Ù‰ ØªØ·ÙˆÙŠØ± ÙˆØ¯Ø¹Ù…Ù†Ù‡Ø¬ Ø¬Ø¯ÙŠØ¯ Ø¹Ù„Ù‰ Ø§Ù„Ù…Ø³ØªÙˆÙ‰ Ø§Ù„Ø¥Ù‚Ù„ÙŠÙ…ÙŠ ÙˆÙ„ÙŠØ³ Ø¹Ù„Ù‰ Ø§Ù„Ù…Ø³ØªÙˆÙ‰ Ø§Ù„Ù…ØÙ„ÙŠ Ù„ØªØÙ‚ÙŠÙ‚ Ø£Ø«Ø§Ø± Ø¥ÙŠØ¬Ø§Ø¨ÙŠØ© Ù„ØÙ…Ø§ÙŠØ© Ø§Ù„ØªÙ†ÙˆØ¹Ø§Ù„ØÙŠÙˆÙŠ ÙˆØ¨Ù…Ø´Ø§Ø±ÙƒØ© ÙˆØ§Ø³Ø¹Ø© Ù…Ù† Ù‚Ø¨Ù„ Ø§Ù„Ù…Ø¤Ø³Ø³Ø§Øª Ø§Ù„Ø¹Ø§Ù…Ø© ÙˆØ§Ù„Ø®Ø§ØµØ© Ù„ØªÙ„Ø¨ÙŠØ© Ø§ØØªÙŠØ§Ø¬Ø§Øª Ø§Ù„ØÙ…Ø§ÙŠØ© Ù…Ù† Ø®Ù„Ø§Ù„ Ø¬Ù‡Ø¯Ø¥Ù‚Ù„ÙŠÙ…ÙŠ Ù…Ù†Ø³Ù‚.